1993
DOI: 10.1136/bmj.307.6909.891
|View full text |Cite
|
Sign up to set email alerts
|

Residence near high voltage facilities and risk of cancer in children.

Abstract: Objective-To investigate whether residence before and after birth near 50 Hz high voltage installations increases a child's risk of cancer and whether risk correlates with the strength of the magnetic field.Design-A population based case-control study. Setting-Denmark.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
127
2
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(134 citation statements)
references
References 11 publications
2
127
2
3
Order By: Relevance
“…Linet et al, 1997 Wire Feychting and Ahlbom, 1993 Calculated fields G 0.2 mT 2.7 1.0-6.3 12. Olsen et al, 1993 Calculated fields G 0.25 mT 1.5 0.3-6.7 13. Verkasalo et al, 1993 Calculated fields G 0.2 mT 1.6 0.3-4.5 14.…”
Section: Methodsmentioning
confidence: 99%
“…Linet et al, 1997 Wire Feychting and Ahlbom, 1993 Calculated fields G 0.2 mT 2.7 1.0-6.3 12. Olsen et al, 1993 Calculated fields G 0.25 mT 1.5 0.3-6.7 13. Verkasalo et al, 1993 Calculated fields G 0.2 mT 1.6 0.3-4.5 14.…”
Section: Methodsmentioning
confidence: 99%
“…However, other epidemiology studies of similar occupational populations have shown negative associations (18,27,53 (48). A high degree of variability in electric and magnetic field exposures has been found in occupational epidemiology studies (14), and a number of confounders that complicate their interpretation have been identified (4,23,34 (17,38,54) or occupational environments (51). The (48).…”
Section: Introductionmentioning
confidence: 99%
“…In EBCLIS, mean 24-h measurements above 0.1 mT in the bedroom and most lived-in room were found in 42% and 44% of homes, respectively; measurements above 0.2 mT at those locations were present in 20% and 22% of homes, respectively; and measurements above 0.3 mT were found in 11% and 14% of homes, respectively. In childhood leukemia studies, the proportion of residences with measurements above 0.1 mT ranged from 0.5% in Denmark (Olsen et al, 1993) to 36% in states in the NCI childhood leukemia study (Linet et al, 1997;Greenland et al, 2000); measurements above 0.2 mT ranged from 0.4% to 12%, respectively; and measurements above 0.3 mT ranged from 0.4% to 6%, respectively.…”
Section: Distribution Of Wire Codes and Magnetic Field Measurementsmentioning
confidence: 99%